Level of knowledge regarding health as well as health education and pro-health behaviours among students of physical education and other teaching specialisations - GRAŻYNA KOSIBA; MARIA GACEK; AGNIESZKA WOJTOWICZ; MAGDALENA MAJER (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: ‪The aim of the study was to assess the relationship between the level of knowledge regarding health and health education as well as the pro-health behaviours of students of physical education and other teaching specialisation. Material and methods: ‪Anonymous and voluntary research was carried out in the years 2013-2014 among a randomly chosen group of Krakow academic youth. The research applied: involved the Inventory of Health Behaviours (IHB) (Polish: Inwentarz Zachowań Zdrowotnych) by Z. Juczyński, a short version of the International Physical Activity Questionnaire (IPAQ) and an original test on knowledge regarding health determinants and education. Results: ‪Research has indicated differences in some health behaviours (IHB) and physical activity (IPAQ) of the students. It was found that along with an increase in the level of knowledge about health and health education, the level of pro-health behaviours, especially regarding healthy eating habits, also increased. However, there were no statistically significant correlations between knowledge about health and health education and the level of physical activity of students of the teaching specialisation. Conclusions: ‪Preparing students - future teachers - for the to implementation of health education at school requires comprehensive impact on various areas of health culture, including the level of knowledge about health determinants, pro-health behaviours, the position of health within one's value system and appropriate methodological competences.